VD_FINDINFO Décision / 2013 / 26 vom 18. Dezember 2012 - VD Tribunal cantonal (2012)
DÉFENSE D'OFFICE, DÉFENSE NÉCESSAIRE, ASSISTANCE JUDICIAIRE | 130 let. b CPP (CH), 132 CPP (CH), 393 al. 1 let. a CPP (CH)